2018
DOI: 10.1016/j.ejca.2018.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Mapping cancer research across Central and Eastern Europe, the Russian Federation and Central Asia: Implications for future national cancer control planning

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…For example, a dedicated cancer research fund is not available in many countries. In addition, the number of clinical trials (in particular early clinical trials and investigator-initiated trials) is lagging in this region [90]. Hence, innovation in prevention, early detection and treatment could have a significant impact on cancer incidence and survival in many Central and Eastern European countries.…”
Section: Inequalities In Researchmentioning
confidence: 99%
“…For example, a dedicated cancer research fund is not available in many countries. In addition, the number of clinical trials (in particular early clinical trials and investigator-initiated trials) is lagging in this region [90]. Hence, innovation in prevention, early detection and treatment could have a significant impact on cancer incidence and survival in many Central and Eastern European countries.…”
Section: Inequalities In Researchmentioning
confidence: 99%
“…To ensure the reliability of the data, we acquired data about funding projects directly from official funding organizations (as shown in the 'Data acquisition and cleaning' of Figure 1). This study could be regarded as a complementary study of previous work using publication data (Begum et al, 2016;Begum et al, 2018;Kalita et al 2015). The two national organizations selected were the NSFC in China and the MRC in the UK.…”
Section: Funding Datamentioning
confidence: 99%
“…Several previous studies have adopted bibliometric methods that rely on publication data to analyze research on disease and its effects on society in various countries/regions (Agarwal & Searls, 2009;Begum et al, 2016;Yegros et al, 2019). For example, Begum et al (2018) mapped research activity using publications and compared the disease burden of different cancers in 29 countries over a 10-year period (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016). Another study using publication data from 2002-2013, which considered outputs and funding related to European noncommunicable respiratory disease and its disease burden, indicated that this was a severely under-researched health condition (Begum et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, several regional and national studies on breast cancer incidence and mortality have been performed, and the results of these multifarious studies from different parts of the world present an inclusive picture. Epidemiological studies from Arab countries [6], India [7], Latin America [8], and Europe [9] show an alarmingly rising burden with associated incidence and mortality. However, specific studies of breast cancer burden at a global level are lacking.…”
Section: Introductionmentioning
confidence: 99%